Evaluation of the relationship between dietary factors, CagA-positive Helicobacter pylori infection, and RUNX3 promoter hypermethylation in gastric cancer tissue - Zhang, Yan-Wei (Baishideng Publishing Group Co., Limited, 2013)
AIM: To evaluate the relationship among Helicobacter pylori (H. pylori) infection, CagA status, and dietary factors with RUNX3 promoter hypermethylation. METHODS: Gastric cancer tissue samples were collected from 184 South Korean patients. All patients were interviewed following a semi-quantitative food frequency questionnaire. The average frequencies of intake and portion sizes of 89 common food items were documented, and total intakes of calories, nutrients, vitamins, and minerals were calculated for each subject. DNA was extracted from gastric cancer tissue samples, and amplification of the HSP60 gene was performed to detect H. pylori infection. Nested polymerase chain reaction (PCR) was used to detect the presence of the CagA gene. RUNX3 gene expression was measured by reverse transcription-PCR, and RUNX3 methylation status was evaluated by methylation-specific PCR. The odds ratios (ORs) and 95%CI associated with RUNX3 promoter hypermethylation status were estimated for each of the food groups, lifestyle factors, and the interaction between dietary and lifestyle factors with CagA status of H. pylori infection. RESULTS: Overall, 164 patients (89.1%) were positive for H. pylori DNA, with the CagA gene detected in 59 (36%) of these H. pylori-positive samples. In all, 106 (57.6%) patients with gastric cancer demonstrated CpG island hypermethylation at the RUNX3 promoter. RUNX3 expression was undetectable in 52 (43.7%) of the 119 gastric cancer tissues sampled. A high consumption of eggs may increase the risk of RUNX3 methylation in gastric cancer patients, having a mean OR of 2.15 (range, 1.14-4.08). A significantly increased OR of 4.28 (range, 1.19-15.49) was observed with a high consumption of nuts in patients with CagA-positive H. pylori infection. High intakes of carbohydrate, vitamin B1, and vitamin E may decrease the risk of RUNX3 methylation in gastric cancer tissue, particularly in CagA- or H. pylori-negative infection, with OR of 0.41 (0.19-0.90), 0.42 (0.20-0.89), and 0.29 (0.13-0.62), respectively. A high consumption of fruits may protect against RUNX3 methylation. CONCLUSION: These results suggest that the CagA status of H. pylori infection may be a modifier of dietary effects on RUNX3 methylation in gastric cancer tissue.